A Bibliometric Analysis of the Landscape of Pediatric Liver Transplantation - Shi, Lei; Zhou, Jie; Jiang, Chenyi; Dai, Wanbing; Yu, Weifeng; Xia, Qiang; Su, Diansan (Frontiers in Pediatrics, 2022)
Background: Nowadays, pediatric liver transplantation (PLT) has become an effective strategy for treating various acute or chronic end-stage liver diseases and inherited metabolic diseases. Many experts have already concluded the current challenges and future directions of PLT. However, no detailed analysis of the publication landscape has substantiated these proposed opinions. Methods: This study presents a bibliometric review of the articles related to PLT between 1997 and 2020. A total of 3084 publications were analyzed mainly by CiteSpace and VOSviewer. Results: The field of PLT has evolved gradually in the past two decades. Articles increased at an average rate of 97 articles every four years. University of Pittsburgh (PITT) is the most prolific institution. The three most productive regions are North America, Europe, and East Asia. Currently, interdisciplinary studies on PLT are scarce. The main goal of PLT has shifted from survival rates to long-term outcome. The quality of life, living donor liver transplantation (LDLT), immunological biomarkers, perioperative hemodynamic management, expanding the indications of PLT, etc. are parts of the emerging research fronts. In the past two decades, articles that contain potentials that may lead to transformative discoveries are scarce, and obvious deficits can be seen in the field of new therapies. Conclusions: Long-term outcome and good quality of life represent the principal direction of work concerning PLT. Deficits in new therapies align with the shortage of intellectual milestones, which indicate possible subsequent intellectual milestones may occur as innovations in therapies such as new immunosuppression therapies or liver cell transplantation.